Transcriptomic Analysis of Long Noncoding RNA and mRNA Expression Profiles in the Amygdala of Rats with Bone Cancer Pain-Depression Comorbidity - Shuyan Wu; Xiaohui Chen; Fengyi Huang; Mingxue Lin; Pinzhong Chen; Haiyang Wan; Fei Gao; Ting Zheng; Xiaochun Zheng (Life, 2021)
Bone cancer pain (BCP)–depression comorbidity has become a complex clinical problem during cancer treatment; however, its underlying molecular mechanisms have not been clarified. Several long noncoding RNAs (lncRNAs) have been demonstrated to be promising therapeutic targets in depression, but research on the role of lncRNAs in BCP–depression comorbidity has been limited. Therefore, high-throughput RNA sequencing was performed to detect differentially expressed profiles in the amygdala of a BCP–depression rat model in this study. We detected 330 differentially expressed mRNAs (DEmRNAs) and 78 differentially expressed lncRNAs (DElncRNAs) in the BCP–depression comorbidity model and then verified the expression of six DEmRNAs and six DElncRNAs with the greatest degrees of difference by RT-qPCR. Furthermore, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed that differentially expressed genes were strongly enriched in inflammatory and immunologic systemic responses. Then the nuclear factor kappa B (NF-κB) signaling pathway and the Th17 differentiation pathway showed significant differences, as determined by Western blot analysis. Finally, we constructed a protein–protein interaction (PPI) network to explore the potential regulatory mechanism of DEmRNAs. In conclusion, our study reveals a new resource for the understanding of dysregulated lncRNAs and mRNAs in BCP–depression comorbidity and provides novel potential therapeutic targets for further approaches.